Fresh frozen plasma transfusion in acute variceal haemorrhage: Results from a multicentre cohort study. (24th May 2021) - Mohanty, Arpan; Kapuria, Devika; Canakis, Andrew; Lin, Honghuang; Amat, Maelys J.; Rangel Paniz, Graziella; Placone, Nicholas T.; Thomasson, Reggie; Roy, Hemant; Chak, Eric; Baffy, Gyorgy; Curry, Michael P.; et al.
Abstract: Background: Fresh frozen plasma (FFP) transfusion is often used in the management of acute variceal haemorrhage (AVH) despite best practice advice suggesting otherwise. Objective: We investigated if FFP transfusion affects clinical outcomes in AVH. Design, setting and patients: We performed a retrospective cohort study of 244 consecutive, eligible patients admitted to five tertiary health care centres between 2013 and 2018 with AVH. Main outcome measurements: Multivariable regression analyses were used to study the association of FFP transfusion with mortality at 42 days (primary outcome) and failure to control bleeding at 5 days and length of stay (secondary outcomes). Results: Patients who received FFP transfusion (n = 100) had higher mean Model for End Stage Liver Disease (MELD) score and more severe variceal bleeding than those who did not received FFP transfusion (n = 144). Multivariable analysis showed that FFP transfusion was associated with increased odds of mortality at 42 days (odds ratio [OR] 9.41, 95% confidence interval [CI] 3.71‐23.90). FFP transfusion was also associated with failure to control bleeding at 5 days (OR 3.87, 95% CI 1.28‐11.70) and length of stay >7 days (adjusted OR 1.88, 95% CI 1.03‐3.42). The independent association of FFP transfusion with mortality at 42 days persisted when the cohort was restricted to high‐risk patients and in patients without active bleeding. Limitations and conclusions: Fresh frozen plasma transfusion in AVH is independently associated with poor clinical outcomes. As this an observational study, there may be residual bias due to confounding; however, we demonstrate no benefit and potential harm with FFP transfusions in AVH.